A Educação Ambiental no contexto da Educação do Campo: estudo de caso sobre o Rio Traíra em Santa Terezinha do Tocantins - Anjos, Elizângela Lopes dos (Universidade Federal do Tocantins, 2022)
This work addresses specific issues related to environmental issues. Thus, it is understood the need to make this discussion from the field of Environmental Education, especially in the context of Rural Education. The evolution of society ended up causing very serious environmental problems, such as deforestation, fires and an increase in the planet's temperature. In this sense, this study aims to highlight the role of Environmental Education in the context of Rural Education as a way of raising awareness about the environmental preservation of the River Traíra in Santa Terezinha do Tocantins. To achieve the research objectives, we used the methodological processes, from exploratory descriptive research, with a qualitative approach, through the case study. To this end, exploratory descriptive research was applied, with a qualitative approach, through the case study. The research applied in the first semester of the year 2020 with 10 students, being 3 students from the 6th year, 3 from the 7th year (both from the Isabel Santana de Freitas Municipal School) and 4 people from the community in general. From the survey, it can be seen that most respondents have difficulties in understanding the theoretical and practical concept of environmental education. As main results, based on the concept presented by the studied authors, we can mention the fact that the concepts regarding environmental education are somewhat vague and confusing. The environmental perception, especially in relation to the Traíras River is also compromised, with contradictions between the answers being seen, such as when asked about the quality and density of the water in the Traíra River. Part of the interviewees understand that their water is clean, while others say it is dirty. Others stated that the river is deep, while others mention its siltation. However, everyone agrees that the river is in a process of degradation, the result of anthropic actions by the community, which can only be reversed with the awareness of everyone.